2019
DOI: 10.1161/jaha.118.010148
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variation in 30‐Day Mortality for Patients With Stroke; The Impact of Individual and Municipal Socio‐Demographic Status

Abstract: Background Thirty‐day mortality after hospitalization for stroke is commonly reported as a quality indicator. However, the impact of adjustment for individual and/or neighborhood sociodemographic status ( SDS ) has not been well documented. This study aims to evaluate the role of individual and contextual sociodemographic determinants in explaining the variation across hospitals in Norway and determine the impact when testing for hospitals with low or high mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In a study on a similar cohort we found income to be more closely associated with post-stroke survival than education [5]. This has also been found in register based studies in Denmark and Norway [6,9]. Based on this we chose to use low income as a proxy for low SES.…”
Section: Data and Variable Definitionsmentioning
confidence: 70%
See 2 more Smart Citations
“…In a study on a similar cohort we found income to be more closely associated with post-stroke survival than education [5]. This has also been found in register based studies in Denmark and Norway [6,9]. Based on this we chose to use low income as a proxy for low SES.…”
Section: Data and Variable Definitionsmentioning
confidence: 70%
“…SES is a multidimensional concept that can be measured in different ways. Several previous studies, including one on a similar cohort, found income to be more strongly associated with post-stroke survival than education [5,6,9]. As we were interested in a general effect of SES, not specifically a pure effect of low income we opted not to adjust for other SES variables, such as education level, in our analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, readmission rates varied from 11.8% to 18% in Norwegian hospitals 4. A reduction in readmission rates and the implementation of well-coordinated transitions between healthcare services have been common goals of Norwegian healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital readmissions are a well-known problem in healthcare services worldwide1–5 with the hospital discharge process as an influential factor 6–8. Hospital discharge procedures play a critical role in the quality of transitional care, specifically on the continuity of information about patients’ treatments, or recommendations for further care 6.…”
Section: Introductionmentioning
confidence: 99%